Effect of fermentation of seed on the chemical properties and fatty acid profile of rubber seed oil - Ugwuanyi J Obeta; Njoku Obioma U (Indian Journal of Natural Rubber Research, 1996)
Rubber (Hevea brasiliensis) seeds were boiled and fermented with mixed culture and pure culture of Bacillus licheniformis. Following fermentation, sapnoifiction value of the oil increased while its iodine value, acid value and unsaponifiable matter decreased; per cent yield of total lipid increased while that of linoleic and linolenic acids decreased. Behenic and myristic acids were undetectable afer fermentation. The implication of these fermentative modifications for the improvement of rubber seed and its oil for human consumption, agricultural and industrial use are discussed.
Keywords: Bacillus licheniformis; Fatty acids; Fermentation; Hevea brasiliensis; Rubber seed oil